An exploratory survey of the needs and adjustment to retirement of persons residing in Port Alfred - Stephens, Brent William (Rhodes University, Faculty of Humanities, Department of Social Work, 1995)
The problem that was chosen to be investigated, was that, within the white middle class South African white-collar worker there appears to be a tendency to live for the "pie in the sky" - which for most seems to be retirement to the idyllic cottage by the sea. Within the South African scenario, there seems to be a definite lack of career planning or at least planning for retirement, other than the financial emphasis. Upon reaching the "ultimate" retirement, retirees take their pension money and move to the coast, expecting pure bliss. The result of their lack of forethought is that they settle in a totally different climate, away from the support of family and friends, possibly finding their income inadequate, with the result that many fall seriously ill, and then discover a lack of geriatric care or a hospital at the time in their lives when they need it the most. The aim of the research was to investigate these issues using a specific location - Port Alfred, researching the fact that Port Alfred continues to be a retirement haven, despite appearing to lack the necessary facilities required by the elderly. The method of the research was to initially administer a pilot questionnaire to a few elderly residents at random, which was then followed up by the formal personally administered questionnaire to a sample. The sample of retired elderly residents in Port Alfred was chosen at random primarily from the various old age homes in Port Alfred. This questionnaire was administered in 1983 but due to financial and personal reasons, the results were not written up. In 1990, the research was continued with a further questionnaire being administered in 1991. The research direction was altered slightly to identify not only what resources were felt to be lacking, but also to identify how well the retired persons of Port Alfred had managed their transition to retirement. The results showed some similarity between the 1983 and the 1991 research. On the surface the retirees appeared well-adjusted and content, but when it was delved deeper, they appeared to have opted out of making any great effort to change their situation, but rather had taken the view that they had earned their rest, would make the best of what they had, and leave it to someone else to champion their cause. This meant that they relied heavily upon those in their community to meet their obvious needs. The promised hospital that they had arduously raised funds for had not materialised, and that seemed to have been the last effort that they had been prepared to make, they were now at rest. The conclusion was that, although the retirees had made the best of their situation, this definitely did not mean that their resources were adequate. Various charities and social services were at work in the community to redress the imbalance, but it was felt that these would in turn benefit by the addition of a social worker. This social worker would coordinate these services and take responsibility for the community at large, particularly addressing the need to unify the services with those to the large non-White community, in the (on-going) development of the New South Africa
Keywords: Retirement, Places of -- South Africa -- Eastern Cape -- Port Alfred; Older people -- South Africa -- Eastern Cape -- Port Alfred -- Social conditions; Older people -- South Africa -- Eastern Cape -- Port Alfred; Older people -- South Africa -- Eastern Cape -- Port Alfred -- Economic conditions; Retirees -- South Africa -- Eastern Cape -- Port Alfred